An Investigatory Project of Ginger (Zingiber Officinale) as an Alternative Anti- inflammatory Massage: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ginger (Zingiber officinale Roscoe), a famous herbaceous plant, has been widely used as aflavoring agent and natural remedy for centuries. Furthermore, the consumption of gingerrhizome is a standard conventional treatment to relieve common health problems, includingpain, nausea, and vomiting. Ginger is quite popular because of an oily component calledgingerol, which gives it its particular sharp and hot flavor. Ginger Anti-Inflammatory MassageOil will specifically benefit those who commonly experience body pain, cramps, andinflammation.Table 10 shows the result of the t-test to see if there is a significant difference in theassessment of evaluated factors between the two groups of massage therapists (M.T.) andchemical engineers (C.E.). For both groups, the overall weighted mean and variance aresupplied, as is the t-critical value with a significance level of 0.5 and degrees of freedom of 8.Is 2.306. For the comparison of the two groups, the computed t-value is 2.547, and thecorresponding p-value is 2.547. Based on these findings, the null hypothesis is accepted,indicating that there is no significant difference in the assessment of the examined variablesbetween the two groups. As a result, the answer is that there is a substantial difference in theratings of the two groups of respondents in terms of the ingredients, procedure, effectiveness,healing duration, and presentation.For further enhancement and improvement of the project, the ensuing discussion and therecommendation proposed are as follows: Regarding ingredients, two of the respondentssuggested using an alternative oil other than olive oil to lower the price. In terms ofprocedures, one respondent suggested letting the oil soak for at least 10 minutes. In terms ofeffectiveness, two of the respondents suggested adding eucalyptus oil and/or methanolcrystal for a cooling effect. In terms of healing duration, one of the respondents suggestedadding other sources of fragrance; in terms of presentation, one of the respondents suggestedstoring the product in a dropper (serum-like) packaging for much more convenient use.
Keywords: Medicine